Best Practices and Challenges of Outcomes Based Education (OBE) in Social Sciences Instruction of Junior High School Students in Jolo, Sulu - Lukman, Adamel K. (HM Publisher, 2021)
Face with the demands of an ever changing global society, our country has in recent years made a shift in its educational landscape. Despite some doubts from the Filipino community, as early as June 2012 we have witness the nationwide implementation of K -12 curriculum in the basic education level as well as the pavement of an outcomes based education for the tertiary level spearheaded by the Commission on Higher Education last 2014. Amidst these swift changes in our education system are the perceived challenges and measures of effectiveness in the implementation of the said programs especially the k – 12 curriculum which is by nature centers on an outcomes based instruction or result – oriented. Corollary to this, there is a present exigency to determine the outcomes based instruction employed by teachers in the high school, its effectives, and perceived challenges. In line with such objectives, this humble work aimed at determining the different strategies used by social sciences teachers at the Mindanao State University – Sulu and the Sulu College of Technology. It also distinguished the level of effectiveness of the OBE strategies in social sciences as perceived by social sciences teachers and students of the two well – known institutions in Sulu. Furthermore, the researcher also looked into the perceived challenges encountered by the respondents in their implementation of an outcomes based instruction.